2022
DOI: 10.3390/ijms23179848
|View full text |Cite
|
Sign up to set email alerts
|

Potential Application of Leelamine as a Novel Regulator of Chemokine-Induced Epithelial-to-Mesenchymal Transition in Breast Cancer Cells

Abstract: CXCR7 and CXCR4 are G protein-coupled receptors (GPCRs) that can be stimulated by CXCL12 in various human cancers. CXCR7/4–CXCL12 binding can initiate activation of multiple pathways including JAK/STAT and manganese superoxide dismutase (MnSOD) signaling, and initiate epithelial–mesenchymal transition (EMT) process. It is established that cancer cell invasion and migration are caused because of these events. In particular, the EMT process is an important process that can determine the prognosis for cancer. Sin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 73 publications
1
4
0
Order By: Relevance
“…These genes have been associated with the JAK/STAT signaling pathway and implicated in the pathogenesis of various diseases. 24 , 25 Consistent with previous research, we identified several genes that could potentially serve as therapeutic targets for EAU, such as Pim1 , which could be inhibited to reduce the proportion of Th17 cells and increase the proportion of Tregs. 26 …”
Section: Resultssupporting
confidence: 87%
“…These genes have been associated with the JAK/STAT signaling pathway and implicated in the pathogenesis of various diseases. 24 , 25 Consistent with previous research, we identified several genes that could potentially serve as therapeutic targets for EAU, such as Pim1 , which could be inhibited to reduce the proportion of Th17 cells and increase the proportion of Tregs. 26 …”
Section: Resultssupporting
confidence: 87%
“…[43,44] It also regulates both intrinsic and extrinsic apoptosis by modulating different factors that include death associated kinase, death receptor fibroblast associated antigen, and B-cell lymphoma 2 family members. [45,46] TGF-𝛽 induces tumor progression by regulating processes like cell proliferation, metastasis, epithelial to mesenchymal transition (EMT). [47] TGF-𝛽 can inhibit the activity of tissue inhibitors by stimulating matrix metalloproteinases (MMP)-2 and MMP-9 thus stimulating tumor progression.…”
Section: Tgf-𝜷 Signaling Pathway: Role In Progression Of Hccmentioning
confidence: 99%
“…[ 49 ] TGF‐β has been found to induce EMT transition which enables the cancer cells to dissociate, penetrate the basal membrane, and undergo metastasis. [ 46 ] TGF‐β expression has been reported to be higher in highly invasive HCC, [ 50 ] and a dramatic increase in serum TGF‐β levels has also been reported in HCC patients. [ 51 ] On a transcriptional level, overexpression of a mutant SMAD‐2 protein can induce SMAD‐3/SMAD‐4 signaling which stimulates the transcriptional induction of VEGF, TGF‐β, and plasminogen activator inhibitor‐one (PAI‐1).…”
Section: Tgf‐β Signaling Pathway: Role In Progression Of Hccmentioning
confidence: 99%
“…In contrast, the DRYLSIT motif was found in CXCR7, and this structural difference resulted in CXCR7's inability to signal through Gαi 40 . In addition, recent studies have also shown that CXCR7 activates intracellular signaling pathways, including protein kinase B (AKT) and JAK/STAT 41 , 42 .…”
Section: Biological Structure and Activation Pathway Of Cxcl12 And It...mentioning
confidence: 99%